Emergency contraception: current options, challenges, and future directions - Dovey S; Sanfilippo J (Dove Medical Press, 2011)
Serena Dovey, Joseph Sanfilippo Magee Women’s Hospital, University of Pittsburgh Medical Center, Pittsburgh, PA, USA Abstract: The term emergency contraception (EC) refers to utilizing a medication or placing a copper intrauterine device within a short time interval after unprotected intercourse in order to prevent pregnancy. Established methods of EC include the Yuzpe regimen, levonorgestrel, and placement of a copper intrauterine device. Recently, ulipristal acetate, a selective progesterone receptor modulator, has been examined in several large-scale clinical trials and been shown to have comparable if not improved efficacy over the levonorgestrel regimen, which is the most commonly used form of EC today. EC has increased in efficacy since its advent with the Yuzpe regimen several decades ago, and many have expressed hope that widespread utilization of EC will lead to a decreased abortion rate worldwide. However, despite increased access to EC over the past several years, many barriers still exist in regards to allowing EC to be widely available to women wishing to prevent unplanned pregnancies. Future research must focus on addressing such barriers in order to realize the potential of EC to decrease abortion rates worldwide. This review article will address the current options for EC, describe current challenges in the field, and highlight future avenues of research. Keywords: emergency contraception, levonorgestrel, ulipristal acetate, Yuzpe regimen